Advances in human factors in simulation and modeling : proceedings of the AHFE 2017 International Conference on Human Factors in Simulation and Modeling, July 17--21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors in Simulation and Modeling, July 17--21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available